2022
DOI: 10.3389/fnins.2022.905247
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget high-definition transcranial direct current stimulation improves response inhibition more than single-target high-definition transcranial direct current stimulation in healthy participants

Abstract: Prior studies have focused on single-target anodal transcranial direct current stimulation (tDCS) over the right inferior frontal gyrus (rIFG) or pre-supplementary motor area (pre-SMA) to improve response inhibition in healthy individuals. However, the results are contradictory and the effect of multitarget anodal stimulation over both brain regions has never been investigated. The present study aimed to investigate the behavioral and neurophysiological effects of different forms of anodal high-definition tDCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 114 publications
(135 reference statements)
1
13
0
Order By: Relevance
“…Additionally, we found that the repeated sessions of multitarget stimulation or SST training alone could improve response inhibition compared with the sham control condition, consistent with our hypothesis. The favorable effect of multitarget stimulation over sham control on response inhibition is in line with our previous study (Guo et al, 2022a). It is also similar to published studies indicating that multitarget stimulation exerted more significant effects on motor function than sham control (Dagan et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, we found that the repeated sessions of multitarget stimulation or SST training alone could improve response inhibition compared with the sham control condition, consistent with our hypothesis. The favorable effect of multitarget stimulation over sham control on response inhibition is in line with our previous study (Guo et al, 2022a). It is also similar to published studies indicating that multitarget stimulation exerted more significant effects on motor function than sham control (Dagan et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Multitarget HD-tDCS was delivered using an M × N-9 HD-tES Stimulator (Soterix Medical, Inc., New York, NY, USA), following the procedures for HD-tDCS usage specified in a previous study protocol ( Villamar et al, 2013 ). The stimulation procedure in this study used multitarget HD-tDCS on rIFG and pre-SMA from our previous study ( Guo et al, 2022a ). The electrodes were localized according to the international 10-10 EEG system ( Jurcak et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A multitarget HD-tDCS study concurrently targeted the right IFG and the pre-supplementary motor area (pre-SMA) and stimulated these brain regions individually for comparison. Results indicate that the combined stimulation of both regions led to improved inhibitory control, while no such improvement was observed when stimulating one single brain region 52 . Here, we tested the impact of net-tDCS optimized to modulate regions important for appetite control, which included parts of the dlPFC, vmPFC, IFG as well as limbic regions important for reward processes and decision making.…”
Section: Discussionmentioning
confidence: 81%